Sexually-transmitted disease prevalence and the factors associated with it in sexually-exploited children in Bogota, Colombia. (2009)
Objective Presenting the characteristics of a group of children who have been sexually exploited in Bogota, determining the prevalence of sexually-transmitted disease (STD) in this group of children and establishing the factors associated with STD in this population. Methodology This was a descriptive, cross-sectional study. The medical charts of children aged 10 to 17 years who sought medical attention at Fundación Renacer between January 2002 and June 2004 were reviewed. The analysis included descriptive statistics, correlations and binomial logistic regression. Results 255 children's charts were included, producing the following characteristics: being female (58.8%), average age was 15.4, 5.9% were affiliated to social security, 89.8% engaged in substance abuse, 41.2% used family planning, 3.9% used a condom during every intercourse and there were 0.86 average pregnancies per female adolescent. Sexually-transmitted disease prevalence was 30.9%. The most common diseases were condilomatosis and Neisseria gonorrhoeae infection. Substance abuse and infrequent condom use were associated with a diagnosis of STD. Conclusion Child sexual exploitation is a reality in Colombia. In spite of the limitations of this study, it can be concluded that STDs are an important problem in the sexually-abused child population in Bogota. Preventing child sexual exploitation and integral attention for these children (including health service provision) must become a priority.